Exploring Senior High School Students’ Engagement In Jigsaw Vocabulary Classroom - Rahayu, Indah Tri; Mobit, Mobit; Wachyudi, Kelik (Jurnal Ilmiah Wahana Pendidikan, 2024)
Vocabulary currently takes essential issue to build communication on in English. Therefore, teachers need to consider a learning strategy which can drive student’s cooperativeness during the learning. This study aims to investigate either the EFL students’ engagement and students’ views on Jigsaw activity in vocabulary learning. The researchers used a descriptive case study as research design. The data was taken observation and interview of 6 senior high school students. The findings demonstrated that the students were actively participating in behavior and action while learning process and exercise. The findings also confirmed that students had certain views regarding vocabulary expansion, social contact, excitement, sentence construction, and challenges.